2016
DOI: 10.4314/bcse.v30i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of pyrimidine carboxamide derivatives catalyzed by uranyl nitrate hexa Hydrate with their antibacterial and antioxidant studies

Abstract: ABSTRACT. An efficient and simple method was developed for the synthesis pyrimidine-5-carboxamides using UO2(NO3)2.6H2O catalyst under conventional and microwave irradiation. The synthesis of dihydropyrimidine using uranyl nitrate had shown many advantages such as easy work up, shorter reaction times and higher yields using acetonitrile as a solvent. The structures of the synthesized compounds were confirmed by FT-IR, 1 H NMR, 13 C NMR and mass spectral data. All the synthesized compounds screened for in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The starting materials were synthesized according to the literature procedure with slight modification explained in the experimental section and their spectroscopic data and melting points compared to those reported in the literature in order to correctly identify the starting materials for the next step of synthesis . The compounds ( 5a–j ) exhibited infrared absorption bands for N−H, P=O and P−C aliphatic bands in the regions 3264–3368, 1232–1238 and 747–758 cm −1 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The starting materials were synthesized according to the literature procedure with slight modification explained in the experimental section and their spectroscopic data and melting points compared to those reported in the literature in order to correctly identify the starting materials for the next step of synthesis . The compounds ( 5a–j ) exhibited infrared absorption bands for N−H, P=O and P−C aliphatic bands in the regions 3264–3368, 1232–1238 and 747–758 cm −1 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Literature is replete with examples showing that heterocycles which incorporate carbazoles [1], azepinones [2] and pyrimidines [3] in their molecular framework display wide range of bioefficacies such as anti-cancer [4], anti-leukemic [5], antiproliferative [6], anti-microbial [7], anti-viral [8], anti-malarial [9], antioxidant [10], etc. Ever since, pyrimidine derivatives have been recognized to belong to the class of 'privileged medicinal scaffolds' [11] its potential have been widely exploited in the discovery of such pyrimidine based drugs as 'Etravirine' [12] which has emerged as a highly potent anti-HIV agent, to have found the FDA approval for the treatment of AIDS.…”
Section: Methodsmentioning
confidence: 99%
“…from easily accessible starting materials, we report herein in this communication, the preliminary results of our study on the synthesis of pyrimidine annulated analogues of carbazolo fused azepinones(8)(9)(10)(11)(12)(13)(14)(15) from 7-ethyl-3,4-dihydroazepino[3,2-b] carbazol-2,5(1H,7H)-dione (3) [18]. A perusal of literature on the preparation of oxoketenedithioacetals, 2-(dimethylaminomethylene) ketones, oxoenolethers and α,βunsaturated ketones (chalcones), demonstrated that these were readily available from the base catalyzed condensation of carbonyl species containing an active methylene group with (i) CS 2 + MeI (ii) DMF-DMA (iii) HCOOEt and (IV) C 6 H 5 CHO respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,3-Thiazine derivatives are class of compounds with potential biological activity, such as growth promoting activities [1], anti-fungal activity [2], antiproliferative [3], anti-tumor activity [4], anticancer [5], analgesic activity [6,7], calming activity [8], anticonvulsant activity [9], antibiotic alctivity [10,11], anti-inflammatory [11,12], antimicrobial [13], antimycobacterial [14], antibacterial [15] and antihypertesive [7,16]. On the other hand, pyrimidine derivatives are known to be biologically active compounds and have shown wide range of biological activities like antitubercular [17], antimicrobial, antioxidant and anti-inflammatory [18][19][20], anticancer [21], analgesic, anti-fungal activity, anti-leishmanial, antiviral activity [22,23]. Recently, our research field focused to design and synthesis of biologically active heterocyclic compounds from readily available reagents [24][25][26].…”
Section: Introductionmentioning
confidence: 99%